Electronic patient-reported outcome measures to enable systematic follow-up in treatment and care of women diagnosed with breast cancer: a feasibility study protocol. Issue 11 (16th November 2022) - Thestrup Hansen, Stine; Piil, Karin; Bak Hansen, Lone; Ledertoug, Karen Marie; Hølge-Hazelton, Bibi; Schmidt, Volker Jürgen
Abstract : Introduction: The use of patient-reported outcome measures (PROMs) in clinical practice has the potential to promote person-centred care and improve patients' health-related quality of life. We aimed to develop an intervention centred around electronic PROMs (ePROMs) for systematic follow-up in patients diagnosed with breast cancer and to evaluate its feasibility. Methods and analysis: We developed a nurse-oriented and surgeon-oriented intervention in PROMs, including (1) an education programme for nurses and surgeons; (2) administration of BREAST-Q as proactive ePROMs during follow-up in patients diagnosed with breast cancer and (3) feedback to nurses and surgeons on PROM scores and a guidance manual for healthcare practitioners. Subsequently, we designed a non-controlled feasibility evaluation on the outcomes acceptability, demand, implementation, practicality and integration. The feasibility evaluation includes qualitative ethnographic studies exploring the user perspectives of patients, nurses and surgeons and quantitative studies to explore the characteristics of the patient population regarding demographic background, response rates and response patterns. The feasibility study was initiated in September 2021, will continue until 2024 and will include approximately 900 patients. EPROMs are collected at the following assessment time points: baseline (after diagnosis, before surgery), 1-year follow-up and 3-year endpoint. Ethics and dissemination: The study will be conducted according to the General Data Protection Regulation and the fifth version of the Helsinki Declaration. The National Committee on Health Research Ethics approved the study according to the law of the Committee § 1, part 4. All data will be anonymised before its publication. The results of the feasibility study will be published in peer-reviewed, international journals.